Rancangan Bangun Company Profile Berbasis Web Pada Smk Istiqomah Muhammadiyah 4 Samarinda (Smk Im 4) - Ahmad Ananda Rifa’I; Justinia Rasyidah Furqan; Kholifah Dwi Annurrahma; Muhammad Raihan; Muhammad Wildan Hadinata; Muhammad Taufiq Sumadi (Jurnal Nusantara Berbakti, 2024)
This research faced challenges in incorporating web design skills into the curriculum of SMK Istiqomah Muhammadiyah 4 Samarinda with limited resources. Through the prototype method and the Figma platform, PKL projects are used to teach students about website development. The aim is to provide relevant skills to the technology and graphic design industries. The steps include requirements analysis, prototyping, user evaluation, and user interface design for the company profile. The result is expected to be a web application that is informative, interesting, and in accordance with the needs of the vocational school.